2018
DOI: 10.1159/000489937
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Deep Brain Stimulation of the Mamillotegmental Fasciculus in Chronic Cluster Headache

Abstract: Background: Deep brain stimulation (DBS) and the proper target for chronic cluster headache (CCH) are still subjects of controversy. Objectives: We present our long-term results of analysis of the target and its structural connectivity. Methods: Fifteen patients with drug-resistant CCH underwent DBS in coordinates 4 mm lateral to the III ventricular wall and 2 mm behind and 5 mm below the intercommissural point. The clinical parameters recorded were the number of weekly attacks, pain intensity, and duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…These findings prompted the use of deep brain stimulation in the posterior hypothalamic grey matter in a patient with intractable CH, and led to a complete relief of attacks (59). To date, nearly 50 operated intractable CH patients, some with a follow-up of more than 4 years, have been reported and showed a significant effect of hypothalamic DBS in about 50-60% of CH patients (60)(61)(62)(63). To understand how hypothalamic DBS may exert its effect, a PET study was applied in hypothalamic deep brain-stimulated patients.…”
Section: Hypothalamic Involvement In Cluster Headache Attacksmentioning
confidence: 99%
“…These findings prompted the use of deep brain stimulation in the posterior hypothalamic grey matter in a patient with intractable CH, and led to a complete relief of attacks (59). To date, nearly 50 operated intractable CH patients, some with a follow-up of more than 4 years, have been reported and showed a significant effect of hypothalamic DBS in about 50-60% of CH patients (60)(61)(62)(63). To understand how hypothalamic DBS may exert its effect, a PET study was applied in hypothalamic deep brain-stimulated patients.…”
Section: Hypothalamic Involvement In Cluster Headache Attacksmentioning
confidence: 99%
“…These studies confirmed the relevance, in CH pathophysiology, of the target-brainstem projections. Notably, different DBS targets were considered: inferior–posterior hypothalamus ( 21 ), midbrain tegmentum ( 28 , 33 ), and ventral tegmental area ( 35 , 52 ). In chronic CH patients, the structural connectivity of these regions also showed extended and relevant connections to pain-related areas, supporting the hypothesis of large pain matrix modulating CH attacks.…”
Section: Dtimentioning
confidence: 99%
“…In particular, important anatomical connections were highlighted between the hypothalamus and the midbrain tegmentum, including the medial lemniscus, the dorsal longitudinal and mamillo-tegmental fasciculi, the fronto-orbital cortex, the reticular shape, and the cerebellar cortex ( 21 , 28 , 33 , 35 ).…”
Section: Dtimentioning
confidence: 99%
“…4 So far, >100 cases of DBS for CCH worldwide have been published, with reports of significant headache reduction in 50 to 100% depending on the chosen outcome measures and selected target. [5][6][7] Despite a growing number of positive case series and prospective trials, the effectiveness of this treatment is still a matter of debate, and the American Headache Society Guideline classified DBS for CCH as level B negative evidence (possibly ineffective). 8 Another area of controversy regarding DBS for CCH refers to the anatomical target for stimulation.…”
Section: Introductionmentioning
confidence: 99%